[tex] \large{ \tt{❃ \: SOLUTION}} : [/tex]
[tex] \underline{ \large{\tt{❁ \: USING \: TWO - POINT \: FORM \: OF \: EQUATION \: OF \: LINE : }}}[/tex]
[tex] \boxed{ \large{ \tt{❈ \: y - y_{1} = \frac{y_{2} - y _{1}}{x_{2} - x_{1}} (x - x_{1})}}}[/tex]
[tex] \large{ \tt{↦y - ( - 1) = \frac{12 - ( - 1)}{ - 7 - ( - 7)} \{x - ( - 7) \}}} [/tex]
[tex] \large{ \tt{↦y + 1 = \frac{12 + 1}{ - 7 + 7}(x + 7)} }[/tex]
[tex] \large \tt \:↦ \: y + 1 = \frac{12}{0} (x + 7)[/tex]
[tex] \large{ \tt{↦ \: y + 1 = 12(x + 7)}}[/tex]
[tex] \large{ \tt{↦y + 1 = 12x + 96}}[/tex]
[tex] \large{ \tt{↦ \: 12x + 96 = y + 1}}[/tex]
[tex] \large{ \tt{↦ \: 12x - y + 96 - 1 = 0}}[/tex]
[tex] \large{ \boxed{ \tt↦12x - y + 95 = 0}}[/tex]
✺ STUDY HARD ! No matter if it seems impossible , no matter if it takes time , no matter if you have to wake up all night , Just remember that the feeling of success is the best thing in the entire world. ♪
۵Hope I helped ! ツ
☼Have a wonderful day / evening ! ☃
# StayInAndExplore ! ☂
▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁